Manajemen Strategi Pondok Pesantren Hafizul Qur’an Al-Ihsan Banjarmasin - Erna Triana; Devi Noviyanti; Raden Yani Gusriani; Nahed Nuwairah (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2022)
This article focuses on strategic management issues carried out by Islamic boarding schools in guiding and making their students become memorizers of the Qur'an and the generation of the Qur'an. The method used in this research is descriptive qualitative. Based on the results of the study, it shows that strategic management has been well implemented by the Hafizul Qur'an Al-Ihsan Banjarmasin Islamic boarding school. This can be seen from the formulation of strategies related to developing vision and mission, identifying external opportunities and threats and determining internal strengths and weaknesses, setting long-term goals and choosing certain strategies to be implemented by Islamic boarding schools. Next is the implementation of the strategy which is the action stage in the form of developing a culture that supports the Islamic boarding school strategy, preparing budgets, developing and empowering information systems and linking employee performance with organizational performance. As well as an evaluation of strategies related to reviewing external and internal factors which form the basis of the current strategy at Islamic boarding schools, measuring performance and taking corrective action.